How the Adaptation of Evolving Technology can cope with the ever changing Demand of Consumers? - Lee, Ehren Sze Tseng; Yazdanifard, Rashad (Journal of Research in Marketing (ISSN: 2292-9355), 2015)
As technology is evolving at a very fast pace, some consideration has to take place in order to meet its customers’ demands. Companies in technology industries have to be able to cope with the demand of the consumers as they slowly progress at their stage of advancement. In this study, it is known that the survivability rate of a company in the technology sector would be based on how capable they are in meeting consumers’ demand. Understanding the demand of the consumer allows them to properly sustain in the market or perish as a result of ignorance. What the study seeks is to understand how they would be able to achieve so.